Pengembangan LKS Berbasis Jucama Untuk Meningkatkan Berpikir Kreatif Matematis - yenni, yenni (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2021)
This research aims to produce a product in the form of a Student Worksheet (LKS) based on the Jucama model, determine the quality of the LKS, and find out whether the LKS can be used to improve high school students' mathematical creative thinking abilities on functional derivative material. The research was conducted at SMA PGRI 83 Legok in the 2020/2021 academic year. The subjects were small-scale limited trials with 8 students from class XII MIPA. The method uses RD, with the ADDIE research model which consists of five steps: (1) analyze, (2) design, (3) development, (4) implementation, (5) evaluation. The student response questionnaire after using the LKS was an average score of 3.1 out of a maximum score of 4 with good assessment criteria. Looking at the indicators of improving students' creative mathematical thinking on the expert assessment sheet, they obtained a score of 4 by achieving a good assessment. Thus, the worksheets developed are good for improving students' creative mathematical thinkingABSTRAKPenelitian ini bertujuan untuk menghasilkan produk berupa Lembar Kerja Siswa (LKS) berdasarkan model Jucama, mengetahui kualitas LKS, serta mengetahui apakah LKS yang dapat dipergunakan untuk meningkatkan kemampuan berpikir kreatif matematis siswa SMA pada materi turunan fungsi. Penelitian dilakukan di SMA PGRI 83 Legok tahun ajaran 2020/2021 Subjek uji coba terbatas berskala kecil dengan 8 orang siswa kelas XII MIPA. Metode menggunakan RD, dengan model penelitian ADDIE yang terdiri dari lima langkah: (1) analyze, (2) design, (3) development, (4) implementation, (5) evaluation. Angket respon siswa sesudah menggunakan LKS berada pada skor rata-rata 3,1 dari skor maksimal 4 dengan kriteria penilaian baik. Melihat indikator meningkatkan berpikir kreatif matematis siswa pada lembar penilaian ahli memperoleh skor 4 dengan mencapai penilaian baik. Dengan demikian LKS yang dikembangkan baik untuk meningkatkan berpikir kreatif matematis siswa